Personalized Risk Assessments in the Criminal Justice System - Goel, Sharad; Rao, Justin M.; Shroff, Ravi (American Economic Review, 2016)
In an effort to bring greater efficiency, equity, and transparency to the criminal justice system, statistical risk assessment tools are increasingly used to inform bail, sentencing, and parole decisions. We examine New York City's stop-and-frisk program, and propose two new use cases for personalized risk assessments. First, we show that risk assessment tools can help police officers make considerably better real-time stop decisions. Second, we show that such tools can help audit past actions; in particular, we argue that a sizable fraction of police stops were conducted on the basis of little evidence, in possible violation of constitutional protections.